The Wild Hunter, the Wandering Jew, and the Flying Dutchman: The Hunt In Wagner’s Der fliegende Holländer - Stephen, J. (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2013)
Richard Wagner’s Der fliegende Holländer is unusual among the composer’s mature operas for the brevity and relative unfamiliarity of its source material. Since the legend of the Flying Dutchman was relatively unknown, both Heine and Wagner contextualize the Dutchman by relating him to better-known figures: Heine refers to the Dutchman as the Wandering Jew, and Wagner, through hunting music, connects him to the Wild Hunter. This article addresses the significance of these associations by examining the meanings of all three legends and demonstrating how they are used by Wagner to provide dramatic and musical structure in the opera.